Kompensasi dalam Meningkatkan Kepuasan Kerja Pegawai Perspektif Ekonomi Islam - Azharudin, Azharudin (EJESH: Jurnal Ekonomi Islam dan Sosial, 2023)
This type of research uses library research, namely research whose object of study uses library data in the form of books, journals, articles as part of the data. Compensation means everything received by employees or employees as remuneration for their work. Compensation is very crucial in an organization or company. Enactment of compensation (wages) because it can increase work performance and motivate employees or employees. Compensation in an Islamic perspective is the price wages paid to workers for their services in the production of wealth similar to other factors of production. Islam shows a very good solution to the wage problem and saves the interests of both parties. Compensation in Islam must be given to employees in return for what has been promised by the employer, the employer will get what will happen from the work that has been done, while the worker will receive wages or compensation for the energy that has been spent. Job satisfaction is one of the most important factors for getting the ultimate work result. When a person feels satisfaction at work, he will make every effort to use all the abilities he has to complete his work assignments. Job satisfaction is a problem that is quite interesting and important for employees, companies and society. Factors that influence job satisfaction are factors related to individuals and related to the organization. Job satisfaction in the Islamic view has been alluded to in the verses of the Qur’an. Similar to the letter at-taubah verse 105, namely "and say, "work you, then Allah will see your work, so will His Messenger and the believers and you will be returned to (Allah) who knows the unseen and the concrete, then he will tell you what you have done." hasibuan said that the needs satisfied by work include: physical and safety needs, social needs and egoistic needs.